2013
DOI: 10.1161/circulationaha.112.000194
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Ventricular Assist Device Therapy as a Bridge to Transplantation Compared With Nonbridged Cardiac Recipients

Abstract: Background-Current available treatment options for advanced heart failure include heart transplantation and ventricular assist device (VAD) therapy. This project aimed to evaluate the cost-effectiveness of a bridge-to-transplantation (BTT)-VAD approach relative to direct heart transplantation in transplant-eligible patients. Methods and Results-A Markov model was used to evaluate survival benefits and costs for BTT-VAD versus nonbridged heart transplant recipients. Three different scenarios were considered acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…Additional outcomes for analysis of cost-effectiveness included ICERs, total cost, and qualityadjusted life years (QALYs) or life years (LYs) gained for VADs compared to OHT. The cost-effectiveness threshold for VADs was set to $100,000 per QALY or LY, below which VADs are considered cost-effective and thus worth paying for (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional outcomes for analysis of cost-effectiveness included ICERs, total cost, and qualityadjusted life years (QALYs) or life years (LYs) gained for VADs compared to OHT. The cost-effectiveness threshold for VADs was set to $100,000 per QALY or LY, below which VADs are considered cost-effective and thus worth paying for (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…derived from government or hospital data (15,22). Time horizons of all studies varied from 20 years (15) to lifetime (6,(22)(23)(24).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Alba and colleagues 10 found that over a 20-year time horizon, using a VAD as a bridge to transplantation increases life expectancy by 1.19 years in high-risk patients at a cost of $100 841, resulting in a cost-effectiveness ratio near $85 000 per life-year gained compared with not using a VAD as a bridge. VADs in lowerrisk patients had worse value with a cost-effectiveness ratio near $120 000 per life-year gained.…”
Section: Articles See P 2414 and P 2424mentioning
confidence: 99%
“…12 Lastly, these devices are costly; establishing the cost-effectiveness of these devices is an essential prerequisite in an era of constrained healthcare resources. 13 We focus predominantly on papers that address these challenges in the following topic review for Circulation: Cardiovascular Quality and Outcomes. We have therefore included papers that evaluate outcomes related to (1) implanted cardioverter-defibrillators, (2) cardiac-resynchronization therapy and (3) ventricular assist devices in patients with cardiomyopathies and its common presentations of heart failure and sudden cardiac death.…”
mentioning
confidence: 99%